Exploring Subaltern Agency in Angelou’s I Know Why the Caged Bird Sings - Awasthi, Prabeen Kumar (Journal of Tikapur Multiple Campus, 2023)
The research paper investigates on the representation of American society that is constituted by the hegemonic social, political and cultural structures of oppression to delimit the identity of African-American women in Angelou’s I Know Why the Caged Bird Sings: An Autobiography. Despite being subordinated by the whites; black women have gained central position in the socio-political spheres in America. This research paper analyzes the bitter experiences of a black girl, Maya Angelou, who is continuously dominated and sexually exploited by white people, and her struggle to overcome the constraints in the existing prejudiced society. The paper uses analytical method and library research in data collection. To analyze the experiences and overcoming of constraints on the part of black women, the research applies the theoretical insights of Gramsci, Fanon, Abrams and Tamen on subaltern, identity, agency and resistance. Broadly, the paper explores the subordination of African- American women and their sheer willpower to resist socio-cultural oppressions for their self-definition as well as social change in America. The research concludes that identity of the subaltern always remains in flux. Proper representation of the subaltern is essential to redefine their identity and to establish them as autonomous individuals in the society.